Analisis Determinan dalam Program Pemberdayaan Masyarakat Tanete Riattang Timur, Kabupaten Bone - Bakar, Andi Abu (GOVERNMENT : Jurnal Ilmu Pemerintahan, 2015)
Abstract: This study aimed to analyze the factors determinant in the implementation of community empowerment policy in Bone regency. Policy National Program for Community Empowerment, (PNPM) rural area experienced various obstacles in its implementation which is characterized by the involvement of the community is not optimal in its implementation of development in rural area as well as the objectives of the program have not been realized as public expectations. The factors supporting the program are: active community involvement in the process of identifying and fixing problems; the effectiveness of the achievement of the benefits of the activity, the benefits of participation RTM, and the benefits of evaluation. The factors inhibiting the program are: non-involvement in the community the planning and establishment of training, the planning and establishment of socialization, planning needs, and the evaluation plan; lack of community involvement in the planning, establishment, and implementation of activities, implementation of the training, address the problem, the implementation of socialization, planning, determination, and participation RTM, the establishment and provision of programs, the establishment and implementation of the evaluation.         Keywords: community involvement, effectiveness, empowerment program. Abstrak: Penelitian ini bertujuan menganalisis faktor-Faktor determinan Program Nasional Pemberdayaan Masyarakat (PNPM) Mandiri Perdesaan di Kecamatan Tanete Riattang Timur, Kabupaten Bone. Kebijakan PNPM mandiri pedesaan mengalami berbagai hambatan yang ditandai dengan keterlibatan masyarakat yang belum optimal serta tujuan program belum tercapai sesuai harapan. Adapun faktor-faktor pendukung yaitu: keterlibatan masyarakat secara aktif dalam proses identifikasi dan penetapan masalah; dan efektifitas pencapaian dari manfaat kegiatan, manfaat partisipasi RTM, dan manfaat evaluasi. Sedangkan faktor-faktor penghambat yaitu: tidak terlibatnya masyarakat dalam perencanaan dan penetapan pelatihan, perencanaan dan penetapan sosialisasi, perencanaan kebutuhan, dan perencanaan evaluasi; rendahnya keterlibatan masyarakat dalam perencanaan, penetapan, dan pelaksanaan kegiatan, pelaksanaan pelatihan, mengatasi masalah, pelaksanaan sosialisasi, perencanaan, penetapan, dan partisipasi RTM, penetapan dan penyediaan kebutuhan program, penetapan dan pelaksanaan evaluasi. Kata kunci: keterlibatan masyarakat, efektifitas, program pemberdayaan